Pluripotency and genetic stability of human pluripotent stem cells - Närvä, Elisa (Annales Universitatis Turkuensis D 1035, 2012)
Pluripotent cells have the potential to differentiate into all somatic cell types. As the adult human body is unable to regenerate various tissues, pluripotent cells provide an attractive source for regenerative medicine. Human embryonic stem cells (hESCs) can be isolated from blastocyst stage embryos and cultured in the laboratory environment. However, their use in regenerative medicine is restricted due to problems with immunosuppression by the host and ethical legislation. Recently, a new source of pluripotent cells was established via the direct reprogramming of somatic cells. These human induced pluripotent stem cells (hiPSCs) enable the production of patient specific cell types. However, numerous challenges, such as efficient reprogramming, optimal culture, directed differentiation, genetic stability and tumor risk need to be solved before the launch of therapeutic applications. The main objective of this thesis was to understand the unique properties of human pluripotent stem cells. The specific aims were to identify novel factors involved in maintaining pluripotency, characterize the effects of low oxygen culture on hESCs, and determine the high resolution changes in hESCs and hiPSCs during culture and reprogramming. As a result, the previously uncharacterized protein L1TD1 was determined to be specific for pluripotent cells and essential for the maintenance of pluripotency. The low oxygen culture supported undifferentiated growth and affected expression of stem cell associated transcripts. High resolution screening of hESCs identified a number of culture induced copy number variations and loss of heterozygosity changes. Further, screening of hiPSCs revealed that reprogramming induces high resolution alterations. The results obtained in this thesis have important implications for stem cell and cancer biology and the therapeutic potential of pluripotent cells.